2017
DOI: 10.1021/acsami.6b12826
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Quantum Dots Incorporated into a Thin Film Nanocomposite Membrane with High Flux and Antifouling Properties for Low-Pressure Nanofiltration

Abstract: Graphene oxide quantum dots (GOQDs), novel carbon-based nanomaterials, have attracted tremendous research interest due to their unique properties associated with both graphene and quantum dots. In the present study, thin film nanocomposite (TFN) membranes comprising GOQDs dispersed within a tannic acid (TA) film were fabricated by an interfacial polymerization reaction for low-pressure nanofiltration (NF). The resultant TA/GOQDs TFN membranes had measurably smoother and more hydrophilic, negatively charged sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(129 citation statements)
references
References 53 publications
6
113
0
Order By: Relevance
“…Through a chemical oxidation process using spent coffee grounds as the carbon source, Xu et al prepared GQDs with a high yield, which were further assembled in membranes with a high degree of oxygenation enabling the efficient removal of a wide range of water pollutants, from organic compounds to heavy metals, with a high flux rate . GQD‐based composite membranes with different polymers have been used for the removal of various industrial dyes, such as Congo red (99.8%), methylene blue (97.6%), methyl orange (99.2%), and rhodamine (99.7%) . They also showed a remarkable desalination efficiency with a water flux of 88.7 L m −2 h −1 bar −1 and highly efficient salt rejection rate of 99%.…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Through a chemical oxidation process using spent coffee grounds as the carbon source, Xu et al prepared GQDs with a high yield, which were further assembled in membranes with a high degree of oxygenation enabling the efficient removal of a wide range of water pollutants, from organic compounds to heavy metals, with a high flux rate . GQD‐based composite membranes with different polymers have been used for the removal of various industrial dyes, such as Congo red (99.8%), methylene blue (97.6%), methyl orange (99.2%), and rhodamine (99.7%) . They also showed a remarkable desalination efficiency with a water flux of 88.7 L m −2 h −1 bar −1 and highly efficient salt rejection rate of 99%.…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Zhang et al [166] fabricated graphene oxide quantum dots (GOQDs) dispersed within thin film nano-composite membrane via interfacial polymerization for low pressure nano-filtration membranes. Their results demonstrated that GOQDs membranes with smooth surface have more hydrophilicity, more porosity, high antifouling property and good stability during the filtration process.…”
Section: Role Of Graphene Oxide In Polymer Nano-composite Membranesmentioning
confidence: 99%
“…In another fabrication approach, g‐C 3 N 4 /rGO was prepared through the in situ polycondensation of cyanamide on the surface of GO sheets . GO quantum dots (GOQDs) have been recently utilized to enhance the performance of membranes . These dots combine the unique properties of both GO and quantum dots and show excellent dispersibility in polymer matrices owing to their particular shape, size, and edge structure.…”
Section: Preparation Of Functionalized Graphenementioning
confidence: 99%
“…The incorporation of GO, rGO/TiO 2 , and GO/ZIF‐8 into the PIP‐/TMC‐based active layer has been reported, and the prepared hybrid membranes showed high Na 2 SO 4 rejection abilities. Zhang et al dispersed GOQD in a TA aqueous solution by means of ultrasonication. The aqueous phase was then reacted with isophorone diisocyanate (IPDI) in organic solution to initiate IP.…”
Section: Preparation Of Functionalized Graphene–polymer Membranesmentioning
confidence: 99%